Soil bacterial community response to continuous cropping of cotton - Ma, Zheng; Li, Peng; Yang, Chuanzhen; Feng, Zili; Feng, Hongjie; Zhang, Yalin; Zhao, Lihong; Zhou, Jinglong; Zhu, Heqin; Wei, Feng (Frontiers in Microbiology, 2023)
Introduction Long-term continuous cropping may result in the outbreak and proliferation of soil-borne diseases, as well as reduction in annual crop production. Overcoming the obstacles of continuous cropping is critical for the long-term growth of modern agriculture. Soil microbes are essential for plant health, but the consequences of continuous cropping on soil microbiome are still poorly understood. Methods This study analyzed changes in soil bacterial community composition of Aksu (AKS) and Shihezi (SHZ) in Xinjiang Province during 1–20 years of continuous cropping by 16S amplicon sequencing. The results showed that the incidence of cotton Verticillium wilt rose with the number of cropping years. The bacterial alpha diversity in the AKS soil grew as the number of continuous cropping years increased, however it declined in the SHZ soil. Results The results of beta diversity analysis showed that there were significant differences in soil bacterial communities between different continuous cropping years and between different soils. The results of community composition changes at the level of main phyla and genus showed that the relative abundance of Actinobacteria, Bacteroidetes and Streptomyces decreased with the increase of continuous cropping years in the AKS and the SHZ soils. In addition, Actinobacteria, Propionibacteriales, and Nocardioidaceae were significantly enriched during the early stages of continuous cropping. Network analysis showed that long-term (≥8 years) continuous cropping interfered with the complexity of soil bacterial co-occurrence networks and reduced collaboration between OTUs. Discussion These findings suggested that continuous cropping and soil origin jointly affected the diversity and structural of bacterial communities, and the loss of Nocardioidaceae and Streptomyces in Actinobacteria might be one of the reasons of continuous cropping obstacles.